Novel FKS1 and FKS2 modifications in a high-level echinocandin resistant clinical isolate of Candida glabrata. Issue 1 (1st January 2019) - Hou, Xin; Healey, Kelley R.; Shor, Erika; Kordalewska, Milena; Ortigosa, Cristina Jiménez; Paderu, Padmaja; Xiao, Meng; Wang, He; Zhao, Ying; Lin, Li-Yan; Zhang, Yan-Hai; Li, Yong-Zhe; et al.
ABSTRACT: Echinocandin resistance in Candida glabrata poses a serious clinical challenge. The underlying resistance mechanism of a pan-echinocandin-resistant C. glabrata isolate (strain L74) was investigated in this study. FKS mutants carrying specific mutations found in L74 were reconstructed by the Alt-R CRISPR-Cas9 system (Fks1 WT/Fks2-E655K, strain CRISPR 31) and site-directed mutagenesis (strain fks1Δ /Fks2-E655K). Sequence analysis of strain L74 revealed a premature stop codon W508stop in FKS1 and an E655K mutation preceding the hotspot 1 region in FKS2 . Introduction of the Fks2-E655K mutation in ATCC 2001 (strain CRISPR 31) conferred a modest reduction in susceptibility. However, the same FKS2 mutation in the fks1Δ background (strain fks1Δ /Fks2-E655K) resulted in high levels of resistance to echinocandins. Glucan synthase isolated from L74 was dramatically less sensitive to micafungin (MCF) relative to ATCC 2001. Both FKS1/FKS2 transcript ratios and Fks1/Fks2 protein ratios were significantly lower in L74 and fks1Δ /Fks2-E655K compared to ATCC 2001 and CRISPR 31 ( P <0.05). Mice challenged with CRISPR 31 and fks1Δ /Fks2-E655K mutants failed to respond to MCF. In conclusion, the high-level of echinocandin resistance in the clinical isolate of C. glabrata L74 was concluded to result from the combination of null function of Fks1 and the point mutation E655K in Fks2.